Ethnic differences in intergenerational housing mobility in England and Wales - Franz Buscha; Emma Gorman; Patrick Sturgis; Min Zhang (Global Labor Organization (GLO), 2023)
In this paper we use linked Census data to document rates of intergenerational housing mobility across ethnic groups in England and Wales. While home ownership has declined across all ethnic groups, we find substantial differences between them, with Black, Pakistani and Bangladeshi households experiencing the strongest intergenerational link between parent and child housing tenure, and Black individuals having the highest rates of downward housing mobility. In contrast, those of Indian origin have homeownership rates similar to White British families, and a weaker link between parent and child housing tenure. These patterns are likely, in turn, to exacerbate existing gradients in other dimensions of ethnicity-based inequality now and in the future.
More recent version: http://hdl.handle.net/10419/273422
Keywords: J62; I24; R31; P46; 330; housing; social mobility; wealth transmission; ethnicity